Analysis of Mapping Regional Tax Potential in Increasing Regional Original Revenue (PAD) in East Lombok Regency in 2019-2023 - Jamilah, Siti Syarohan; Manan, Abdul; Agustiani, Eka (Westscience Press, 2025)
This study aims to analyze the potential of regional tax revenue in increasing Regional Original Revenue (PAD) in East Lombok Regency in 2019-2023. This study uses a quantitative descriptive approach. The data analysis technique in this study is the analysis of regional tax revenue reports using the Klassen Typology method. The results of the study show that by using the Klassen Typology method, the types of taxes that are included in the Prima/Superior sector are Hotel, Restaurant, Billboard, Street Lighting, Non-Metallic Minerals and Rocks, and Land and Building Rights Acquisition Duty Tax. The types of taxes that are included in the Developing sector are Entertainment, Parking, and Groundwater Tax. The type of tax that is included in the Potential sector is the Rural and Urban Land and Building Tax. Then the type of tax that is included in the Underdeveloped sector is the Swallow's Nest Tax. In the future, the Regional Government of East Lombok Regency is expected to carry out a policy of intensification and extension of the existing regional tax potential to optimize the increase in the tax realization rate, so that the tax revenue figure is in accordance with the potential that should be generated and regional taxes can make a large contribution to the Regional Original Revenue.